Revision of section Setacea of the genus Batrachospermum (Batrachospermales, Rhodophyta) with emphasis on specimens from Brazil - Rossignolo, Natalia L. [UNESP]; Necchi, Orlando [UNESP] (Int Phycological Soc, 2016)
This study evaluated the species level taxonomy and phylogenetic relationships among species of the section Setacea of the genus Batrachospermum. Molecular data (sequences of the plastid-encoded RuBisCO large subunit gene, rbcL; and the barcode region of the mitochondrial gene that encodes the cytochrome c oxidase subunit 1, cox1) were generated and morphological characters described for 15 populations from Brazil, Japan and Spain. The analyses of rbcL sequences revealed that section Setacea forms a well-supported clade, which was positioned close but clearly separated from some species of Batrachospermum usually called group 'Australasica'. Three well-supported clades were formed within the section: Batrachospermum sp. from Brazil; Batrachospermum atrum from Australasia, Europe and Asia and Batrachospermum puiggarianum from South America. The analyses of cox1 sequences revealed two well-supported groups: a large group with the sequences of B. puiggarianum from Brazil and a small group with one sequence of B. atrum from Spain and two sequences of Batrachospermum sp. from Brazil. The interspecific variation among these three species was high (38-71 bp, 3.0-5.5% for rbcL; 37-51 bp, 5.6-7.5% for cox1); whereas, sequence divergences within these three clades were much lower (0-33 bp, 0-2.6% for rbcL; 0-15 bp, 0-2.3% for cox1). The section is raised to genus (Setacea), and three species were recognized, including two previously described species (Setacea atra and Setacea puiggariana) that can be separated by either molecular and morphological data. A third species could not be distinguished from S. atra by morphological evidence but is clearly distinct based on divergence levels of both molecular markers used in this study (5.6-6.2% for rbcL; 3.0-3.4% for cox1) and is proposed as a new species (Setacea atro-brasiliensis) with the known geographic distribution restricted to Brazil.
Keywords: Batrachospermales; Batrachospermum; Brazil; cox1; rbcL; Setacea; Setacea atro-brasiliensis